An investigation into treatment administration and survival for people with small cell lung cancer - Jones, Gavin Stewart (2019)
Background Chemotherapy is the backbone of treatment for small cell lung cancer (SCLC) but this may change in the future with the emergence of immunotherapy. Current recommendations state performance status (PS) and comorbidity should be used as measures to decide whether chemotherapy is appropriate but in some circumstances this decision comes down to whether the patient is fit enough to withstand its toxicity. Thoracic radiotherapy and prophylactic cranial irradiation (PCI) are adjuncts to chemotherapy and can cause additional side effects, impacting quality of life. This is an important factor to consider as median survival is short. Furthermore, the efficacy of PCI has been questioned in extensive disease (ED-SCLC). In order to deliver effective treatment it is important that clinicians are aware of the short-term risks and long-term survival gains of these therapies so that a balanced, objective decision can be made before treatment is administered.